Ongoing Debate on Medically-Assisted Death in Canada - Khattra, Ruhani; Kim, Olivia; Lu, Jia (The Meducator, 2024)
In 2016, Canada introduced Bill C-14, the Medical Assistance in Dying (MAiD) Act, providing an end-of-life care option for a rapidly increasing number of Canadians. MAiD includes active and passive methods, known as voluntary euthanasia – administered by a designated medical professional – and assisted suicide – the provision of medication by a medical professional to self-administer. The House of Commons and Senate passed Bill C-14 following The Supreme Court’s unanimous decision in Carter v Canada. This case challenged the prohibition of physician-assisted death, decreeing it an infringement on the Canadian Charter of Rights and Freedoms.